Dynamics of Charcoal Alteration in a Tropical Biome: A Biochar-Based Study - Ascough, Philippa L.; Bird, Michael I.; Meredith, William; Snape, Colin; Large, D.; Tilston, Emma; Apperley, David; Bernabé, Ana; Shen, Licheng (Frontiers in Earth Science, 2018)
Pyrogenic carbon (PyC) is a polyaromatic residue of the incomplete combustion of biomass or fossil fuels. There is a growing recognition that PyC forms an important part of carbon budgets, due to production rates of 116–385 Tg C yr, and the size and ubiquity of PyC stocks in global carbon reservoirs. At least a proportion of PyC exists in a highly recalcitrant chemical form, raising the prospect of long-term carbon sequestration through soil amendment with ‘biochar’, which is generally produced with the aim of making a particularly recalcitrant form of PyC. However, there is growing evidence that some PyC, including biochar, can be both physically and chemically altered and degraded upon exposure to the environment over annual timescales, yet there is a lack of information concerning the mechanisms and determining factors of degradation. Here, we investigate three main factors; production temperature, feedstock composition, and the characteristics of the environment to which the material is exposed (e.g. pH, organic matter composition, oxygen availability) by analysis of biochar samples in a litterbag experiment before and after a year-long field study in the tropical rainforests of northeast Australia. We find that non-lignocellulosic feedstock has lower aromaticity, plus lower O/C and H/C ratios for a given temperature, and consequently lower carbon sequestration potential. The rate at which samples are altered is production temperature-dependant; however even in the highest temperature samples loss of the semi-labile aromatic carbon component is observed over one year. The results of 13C-MAS-NMR measurements suggest that direct oxygenation of aromatic structures may be even more important than carboxylation in environmental alteration of biochar (as a subset of PyC). There is a clear effect of depositional environment on biochar alteration even after the relatively short timescale of this study, as changes are most extensive in the most oxygenated material that was exposed on the soil surface. This is most likely the result of mineral ingress and colonization by soil microbiota. Consequently, oxygen availability and physical or chemical protection from sunlight and/or rainwater is vital in determining the alteration trajectory of this material.